Tanggung Jawab Pemegang Saham Atas Penerbitan Faktur Fiktif (Jurnal Sosial Humaniora dan Pendidikan, 2025)
As a legal entity, a limited liability company ("company") is entitled to issue tax invoices. However, there have been cases where shareholders issue fictitious tax invoices on behalf of the company. This study aims to analyze the legal responsibility of shareholders in the issuance of fictitious tax invoices by the company. Using doctrinal research with a descriptive-analytical approach, the findings of this study indicate that if there is evidence of abuse of the company for the purpose of issuing fictitious tax invoices, shareholders are legally responsible for the issuance of such invoices, which result in financial harm to the state